Chlorinated isomers of nonylphenol differ in estrogenic and androgenic activity - Cormio, Paola Giulia; Christmann, Mathias; Rastall, Andrew; Grund, Stefanie; Hollert, Henner; Schuphan, Ingolf; Schmidt, Burkhard (Journal of environmental science and health. Part A, Toxic, 2011)
Technical mixtures of nonylphenol (NP) contain over 20 p-substituted isomers. Mono- and di-chlorinated derivatives are generated during the chlorination process in water treatment. Four NP isomers (i.e. 4n-, p353-, p33-, p363-NP) and their mono- (MCl) and di-chlorinated (DCl) derivatives were tested for their estrogenic and androgenic potency using yeast estrogenic and androgenic assay. The p353-NP and 4n-MClNP isomers showed the highest and the lowest estrogenic potency, respectively. The p363-MClNP exhibits estrogenic potency comparable to the parent isomer, whereas all p-DClNP compounds displayed a decrease in the estrogenic potency. In the anti-androgenic screen, all substances exhibited a positive response; the mono- and di-chlorinated derivatives exhibit lower potency than the parent isomers. The isomer p363-NP and its corresponding mono- and di-chlorinated derivatives were almost inactive. Furthermore, all compounds were tested for anti-estrogenic and androgenic assays, but none of them showed a positive response. These results indicate that for assessing the xeno-hormone potency of chlorinated derivatives of NP, the use of pure compounds is essential because the mixtures are not representative. In fact the concentrations of NP isomers differ in technical mixtures according to the producers; after chlorination different technical mixtures can generate dissimilar ratios of chlorinated derivatives. Finally, the chlorinated derivatives of NP didn’t show an increase in xeno-hormone potency compared to the parent isomers, and for this reason the many oxidized by-products generated during chlorination process mask the xeno-hormone potency of the pure chlorinated isomers of NP.
Gesehen am 12.04.2022